The Influence of Price, Location and Service Quality on Purchasing Decisions - Khanifah, Siti Nur; Alim, Muchammad Rully Sjahirul (Economics and Business International Conference Proceeding, 2024)
The aim of this research is to identify how price, location and service quality influence customer satisfaction at Sunset View Cafe for the needs of the company and consumers. The total population in this study was 10,498 people, while the sample was calculated using the Slovin formula, which resulted in a sample size of 99 respondents. The sampling technique used was purposive sampling itative analysis. Hypothesis testing uses the t test, F test, and Determination test. Apart from that, the data normality test, multicollinearity test and heteroscedasticity test were also used. Price has no negative and significant effect on purchasing decisions. Location has no effect on purchasing decisions. Service quality has a positive effect on purchasing decisions.